Plant cell suspension culture of Thevetia peruviana (Pers.) K. Schum. in shake flask and stirred tank reactor scale: A comparative study (2017)
ABSTRACT: The aim of this work was to evaluate the effect of changing the shake flask for a stirred-tank bench bioreactor on the performance of Thevetia peruviana cultures. Maximum cell growth of 18.59 and 8.46 g DW/L for shake flask and bench bioreactor at day 14 was obtained, respectively. The end of the exponential growth phase in shake flask was correlated with total sugar consumption, while this behavior was not observed in bench bioreactor. Preferential uptake of glucose over fructose was observed in both systems. Cell morphology was similar for both systems during culture time, exhibiting individual cells with cylindrical and elongated shape at day 0 and some aggregates with rounded cells at day 14. Polyphenol production was not affected by the system configuration and scale. Intra and extracellular antioxidant activity were directly related with phenol production in both systems. Guaiacol peroxidase activity (GPX) went from 1.87 to 7.97 µM/min/mg protein in shake flask and it correlated with low reactive oxygen species (ROS) production. This is an indication of a positive enzymatic cell response for culture in shake flask mediated by GPX. In contrast, the conditions in the bench bioreactor generated a higher stress environment, increasing ROS production without activating enzymatic or non-enzymatic responses led by guaiacol and phenolic compounds, respectively. In conclusion, bench stirred-tank bioreactor scale affects biomass production and sugars uptake negatively.